2012
DOI: 10.1063/1.4748286
|View full text |Cite
|
Sign up to set email alerts
|

Device convolution effects on the collective scattering signal of the E × B mode from Hall thruster experiments: 2D dispersion relation

Abstract: The effect of the collective light scattering diagnostic transfer function is considered in the context of the dispersion relation of the unstable E Â B mode previously reported. This transfer function is found to have a contribution to the measured frequencies and mode amplitudes which is more or less significant depending on the measurement wavenumbers and angles. After deconvolution, the experimental data are found to be possibly compatible with the idea that the mode frequency in the jet frame (after subtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…These assumptions are consistent with the experimental results as shown in Ref. 4 and are also consistent with the numerical study of the mode performed in Sec. V where it has been shown that the Doppler effect provides the dominant contribution to the angular frequencies when a is varied.…”
Section: B Analytical Model Fitted To the Experimental Dispersion Resupporting
confidence: 88%
See 1 more Smart Citation
“…These assumptions are consistent with the experimental results as shown in Ref. 4 and are also consistent with the numerical study of the mode performed in Sec. V where it has been shown that the Doppler effect provides the dominant contribution to the angular frequencies when a is varied.…”
Section: B Analytical Model Fitted To the Experimental Dispersion Resupporting
confidence: 88%
“…a) Electronic address: jordan.cavalier@ijl.universite-nancy.fr. 4. electron dynamics are described using the Vlasov equation.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations were successful from that point of view. Recent experiments using collective Thomson scattering have confirmed the existence of this instability [6][7][8][9] immediately at the exit of the thruster.…”
Section: Introductionmentioning
confidence: 74%
“…The transition to a modified ion-acoustic instability has been experimentally investigated by Barrett et al [11] and analytically studied by Gary and Sanderson [10]. More recently, Cavalier et al [12][13] and Lafleur et al [14][15][16] have solved the dispersion relation for typical Hall thruster conditions.…”
Section: Introductionmentioning
confidence: 99%